Highly Efficient Transition Metal Nanoparticle Catalysts in Aqueous Solutions. Issue 9 (28th January 2016) - Wang, Changlong; Ciganda, Roberto; Salmon, Lionel; Gregurec, Danijela; Irigoyen, Joseba; Moya, Sergio; Ruiz, Jaime; Astruc, Didier
Abstract: A ligand design is proposed for transition metal nanoparticle (TMNP) catalysts in aqueous solution. Thus, a tris(triazolyl)‐polyethylene glycol (tris‐trz‐PEG) amphiphilic ligand, 2, is used for the synthesis of very small TMNPs with Fe, Co, Ni, Cu, Ru, Pd, Ag, Pt, and Au. These TMNP‐2 catalysts were evaluated and compared for the model 4‐nitrophenol reduction, and proved to be extremely efficient. High catalytic efficiencies involving the use of only a few ppm metal of PdNPs, RuNPs, and CuNPs were also exemplified in Suzuki–Miyaura, transfer hydrogenation, and click reactions, respectively. Abstract : A tip of the cap : A water‐soluble tris‐(triazolyl)‐polyethylene glycol amphiphilic ligand encapsulates and stabilizes transition metal nanoparticle catalysts. The capping ligands allow for highly efficient nitro‐arene reduction, click, Suzuki–Miyaura, and transfer hydrogenation reactions.